2022
DOI: 10.1186/s13287-022-02813-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free fat extract attenuates osteoarthritis via chondrocytes regeneration and macrophages immunomodulation

Abstract: Background The prevalence of osteoarthritis (OA) is increasing, yet clinically effective and economical treatments are unavailable. We have previously proposed a cell-free fat extract (CEFFE) containing multiple cytokines, which possessed antiapoptotic, anti-oxidative, and proliferation promotion functions, as a “cell-free” strategy. In this study, we aimed to evaluate the therapeutic effect of CEFFE in vivo and in vitro. Methods In vivo study, sod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…[ 29 ] Jia et al found that CEFFE inhibited osteoarthritis progression via promoting cartilage regeneration and limiting joint inflammation. [ 30 ] These findings highlight the multifaceted impact of CEFFE on bone homeostasis. In addition, CEFFE could also enhance soft tissue regeneration and even rejuvenate aging cells.…”
Section: Discussionmentioning
confidence: 96%
“…[ 29 ] Jia et al found that CEFFE inhibited osteoarthritis progression via promoting cartilage regeneration and limiting joint inflammation. [ 30 ] These findings highlight the multifaceted impact of CEFFE on bone homeostasis. In addition, CEFFE could also enhance soft tissue regeneration and even rejuvenate aging cells.…”
Section: Discussionmentioning
confidence: 96%
“…This benefited for not only the growth and functional expression of ECs but also modulating macrophages into the anti-inflammatory phenotype, as also confirmed in our study (Figure S5). It is likely that the presented multiple growth factors in FE may function synergistically to stimulate vascularization. While it is the previously demonstrated pro-angiogenic effect of FE that initiated our current effort for engineering pro-vasculogenic fibers, increasing evidence suggests that our FE, derived from healthy young women of different ages (22–35 years old) , in different locations of the body (e.g., abdomen, thighs, and upper arms) with relatively stable concentrations of the major growth factors, has omnipotent biological functions in the treatment of different diseases, such as ischemic stroke, osteoporosis, osteoarthritis, spinal cord injuries, chronic wound healing, reproductive related disorders, , and so on. With the multifaceted actions identified in FE, in tandem with its cell recruitment capability observed in our current study (Figures E,F and S1) and elsewhere, the FE-PDA@PCL/GT fiber system will be well suitable for engineering 3D fibrous scaffolds , for in situ regeneration of different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CEFFE attenuates osteoarthritis via chondrocyte regeneration and macrophage immunomodulation. 192 In addition, PRP may promote AC lubrication and regeneration, and retards the progression of OA by stimulating cell migration, proliferation, differentiation of progenitor/MSCs, joint homeostasis, and joint lubrication. 193 , 194 The function of BMSCs extracted exosomes was verified in vitro and in OA model in vivo.…”
Section: Articulate Cartilage Defects Therapeutic Strategiesmentioning
confidence: 99%